Chronicles from Kashmir an annotated, multimedia script - Dinesh, Nandita; Open Book Publishers (Open Book Publishers, 2020)
"'What is happening in Kashmir?' Chronicles from Kashmir explores this question through a site-adaptive 24-hour theatrical performance. Developed between 2013 and 2018 by the Ensemble Kashmir Theatre Akademi and Nandita Dinesh, the play uses a durational, promenade format to immerse its audience within a multitude of perspectives on life in Kashmir. From a wedding celebration that is interrupted by curfew, to schoolboys divided by policing strategies, and soldiers struggling with a toxic mixture of boredom and trauma, Chronicles from Kashmir uses performance, installation and collaborative creation to grapple with Kashmir's conflicts through the lenses of outsiders, insiders, and everyone in between. Due to varying degrees of censorship and suppression, the play has not been performed live since 2017. This book is, therefore, an attempt to keep Chronicles from Kashmir alive by including filmed scenes, a script, contextual questions, a glossary, and illuminating introductions by Nandita Dinesh and EKTA founder Bhawani Bashir Yasir. A valuable Open Access resource for practitioners, educators and students of performance and conflict, this book is also stimulating reading for anybody who has asked, 'What is happening in Kashmir?' This playscript includes: Twenty filmed scenes of the play in performance ; A range of contextual questions to stimulate discussion on staging site-adaptive theatre in places of conflict ; A helpful glossary."--Publisher's website.
Contents -- Videos: Chronicles from Kashmir -- GLOSSARY -- Summaries and Deconstructions / Nandita Dinesh ; The Schedule / Nandita Dinesh ; The Journey Begins / Nandita Dinesh ; Scene 0: Framing the Experience / Nandita Dinesh ; Scene One: The Experiment / Nandita Dinesh ; Scene Two: The Departure / Nandita Dinesh ; Scene Three: The Man & the Woman / Nandita Dinesh -- INSTALLATION A / Nandita Dinesh ; Scene Four: The Artists / Nandita Dinesh ; Scene Five: The Puppets / Nandita Dinesh -- INSTALLATION A / Nandita Dinesh ; Scene Six: The Incarcerated / Nandita Dinesh ; Scene Seven: The Soldiers / Nandita Dinesh ; Scene Eight: The Argumentation Cultures / Nandita Dinesh ; The First Coalition / Nandita Dinesh ; Scene Nine: The Sikhs / Nandita Dinesh ; Scene Ten: The Apples / Nandita Dinesh -- INSTALLATION A / Nandita Dinesh ; The Second Coalition / Nandita Dinesh ; Scene Eleven: The Village-City Love Affair / Nandita Dinesh -- A WEDDING and a CURFEWED NIGHT / Nandita Dinesh ; Scene Twelve: The Mirrors & a Poetic Lament / Nandita Dinesh ; The Third Coalition / Nandita Dinesh ; Scene Thirteen: The Pelters / Nandita Dinesh ; Scene Fourteen: The Banalities / Nandita Dinesh ; Scene Fifteen: The Time / Nandita Dinesh -- INSTALLATION A / Nandita Dinesh ; Scene Sixteen: The Women / Nandita Dinesh ; Scene Seventeen: The Game Show / Nandita Dinesh -- INSTALLATION A / Nandita Dinesh ; Scene Eighteen: The Hideout / Nandita Dinesh ; Scene Nineteen: The Return / Nandita Dinesh ; Scene Twenty: The Seesaws / Nandita Dinesh ; Scene Twenty-One: The Disappeared & the Police / Nandita Dinesh ; Scene Twenty-Two: The Hope / Nandita Dinesh ; The Last Coalition / Nandita Dinesh -- Bibliography -- About the Team.
Available through Open Book Publishers.
Links to videos are available from the Additinal Resources tab on the publisher's website.
Includes bibliography (pages 231-234).
Mode of access: World Wide Web.
Keywords: Kashmir, Vale of (India) -- Politics and government; Kashmir, Vale of (India) -- Social conditions; Kashmir, Vale of (India) -- Social life and customs